Upaya Melawan Stereotip dengan Membangun Minat Matematika Menggunakan Strategi Inovatif Untuk Anak Sekolah Dasar Di SD Negeri 05 Pemulutan - Haryanti, Lisa (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2024)
Gender stereotypes in mathematics education have long been a concern in the field of education. Although empirical evidence shows that there are no inherent differences in mathematical abilities between boys and girls, these stereotypes persist in culture and society. The impact is particularly significant, especially on elementary school children, who tend to have low interest and confidence in mathematics. However, innovative strategies such as the Problem Solving approach can address these stereotypes and help build strong interest and skills in mathematics. Through observation and evaluation, it was found that the implementation of innovative strategies has a significant positive impact on students' interest and achievement in mathematics. Therefore, continuous efforts to combat stereotypes, foster interest in mathematics, and implement innovative strategies are crucial in creating a supportive learning environment that advances students' mathematical abilities